Vaccine immune response and interference of colostral antibodies in calves vaccinated against rabies at 2, 4 and 6 months of age born from antirabies revaccinated females - Filho, O. A. [UNESP]; Megid, Jane [UNESP]; Geronutti, L. [UNESP]; Ratti, J.; Almeida, M. F. A.; Kataoka, A. P. A. G.; Martorelli, L. F. A. (Elsevier B.V., 2012)
Considering the high prevalence of rabies in cattle, we aimed to evaluate the interference of colostral antibodies transferred to calves after birth and the benefit of administering an antirabies vaccination in two-month-old calves compared to vaccinating at 4 and 6 months of age. Calves born from females revaccinated against rabies during the third trimester of pregnancy were studied. Forty-eight hours after parturition, blood samples from dams and offspring were collected, and antirabies neutralizing antibody titers were analyzed using the Rapid Focus Fluorescent Inhibition Test. We found that all calves had similar titers of antibodies transferred through the colostrum. Furthermore, none of the calves presented a satisfactory serological response after the first vaccination, but all had an appropriate response after revaccination. This study demonstrates that antirabies vaccination should be recommended for calves at two months of age in endemic and epizootic situations. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Rabies; Vaccination; Colostral antibodies; Humoral immune response; Cattle; Calves